Electro-photographic member, heating and fixing device, and electro-photographic image forming apparatus

By adjusting the crosslinking structure of silicone rubber and the arrangement of fillers, the tensile modulus of the elastic layer is reduced and the crosslinking structure is reconstructed at high temperatures, the problems of increased thermal conductivity and hardness are solved, and the stability and durability of electrophotographic image formation are achieved.

JP2025018226APending Publication Date: 2025-02-06CANON KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023121745
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

The prior art is difficult to suppress the increase in the hardness of the elastic layer while improving the thermal conductivity, and the elastic layer is prone to fracture or plastic deformation during long-term use.

Method used

By adjusting the crosslinking structure and filler arrangement of the silicone rubber, the tensile modulus of the elastic layer is reduced to 0.20 MPa or less, and the crosslinking structure is reconstructed in a high temperature environment to maintain low hardness. Combined with the arrangement of the thermally conductive filler in the thickness direction, the flexibility and durability of the elastic layer are ensured.

Benefits of technology

The low hardness and high durability of the elastic layer under high temperature environment are achieved, high-quality electrophotographic image formation is ensured, and breakage or plastic deformation of the elastic layer is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018226000001_ABST
    Figure 2025018226000001_ABST
Patent Text Reader

Abstract

To provide an electro-photographic member that achieves a low hardness state while ensuring the thermal conductivity and durability in the thickness direction of a fixing member elastic layer.SOLUTION: An electro-photographic member includes a substrate and an elastic layer on the outer peripheral surface of the substrate. The elastic layer contains silicone rubber. A tensile elastic modulus in the direction perpendicular to the thickness direction of the elastic layer is 0.20 MPa or less. A compressive elastic modulus in the thickness direction of the elastic layer is 0.19 to 0.57 MPa. A value of a ratio of the tensile elastic modulus in the direction perpendicular to the thickness direction to the compressive elastic modulus in the thickness direction of the elastic layer (tensile elastic modulus / compressive elastic modulus) is 0.80 or less. A compressive elastic modulus reduction rate in direction corresponding to the thickness direction of the elastic layer of a sample sampled from the elastic layer satisfies a prescribed condition.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electrophotographic member used in an electrophotographic image forming apparatus such as a copying machine or a printer, and to a heat fixing device and an electrophotographic image forming apparatus that include the electrophotographic member. [Background technology]

[0002] In a thermal fixing device of an electrophotographic image forming apparatus, a pressure contact section is composed of a heating member and a pressure member disposed opposite the heating member. When a recording material (such as paper) holding an unfixed toner image is introduced into the pressure contact section, the unfixed toner is heated and pressurized, the toner is melted, and the image is fixed to the recording material. The heating member is a member that comes into contact with the unfixed toner image on the recording material, and the pressure member is a member disposed opposite the heating member. The fixing member according to the present disclosure includes a heating member and a pressure member. The fixing member may have a shape of a roller or an endless belt that is rotatable. These fixing members include those having an elastic layer containing, for example, a rubber such as crosslinked silicone rubber and a filler on a base body formed of metal or heat-resistant resin. In recent years, there has been a demand for further improvement in thermal conductivity in the thickness direction of the elastic layer of a fixing member in order to increase print speed, improve image quality, etc. Patent Document 1 discloses a fixing member in which the thermally conductive filler contained in the elastic layer is a blend of large and small particle diameters, thereby suppressing an increase in hardness of the elastic layer and increasing thermal conductivity.

[0003] Patent Document 2 discloses a fixing member in which the alignment of large particle size fillers in the elastic layer in the thickness direction of the elastic layer is suppressed, while small particle size fillers present between the large particle size fillers are aligned in the thickness direction of the elastic layer to form a heat conduction path, thereby reducing the content of heat conductive filler and increasing the heat conductivity of the elastic layer in the thickness direction. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2005-300591 A [Patent Document 2] JP 2019-215531 A Summary of the Invention [Problem to be solved by the invention]

[0005] According to the study by the present inventors, in the fixing member according to Patent Document 1, when the thermal conductivity in the thickness direction of the elastic layer is to exceed 1.5 W / (m·K), the filler content relative to the silicone rubber needs to be 60% by volume or more. Therefore, it is considered that it is difficult to obtain a fixing member that achieves higher thermal conductivity while suppressing an increase in hardness by the invention according to Patent Document 1. In addition, in the fixing member according to Patent Document 2, it is possible to further improve the thermal conductivity in the thickness direction while suppressing an increase in hardness of the elastic layer. Here, the present inventors have produced and studied a fixing member in which the crosslinking degree of the silicone rubber in the elastic layer is reduced in order to further reduce the hardness of the elastic layer of the fixing member according to Patent Document 2. Specifically, a fixing member in which the compressive elastic modulus in the thickness direction of the elastic layer is soft, such as 0.19 to 0.57 MPa, was studied. As a result, when the fixing member according to the above study was used for forming electrophotographic images for a long period of time, breakage or plastic deformation occurred in the elastic layer.

[0006] At least one aspect of the present disclosure is directed to providing a fixing member having low hardness and excellent durability. At least one aspect of the present disclosure is directed to providing a heat fixing device that contributes to the stable formation of high-quality electrophotographic images. At least one aspect of the present disclosure is directed to providing an electrophotographic image forming apparatus that can stably form high-quality electrophotographic images. The present invention is aimed at providing a synthesis device. [Means for solving the problem]

[0007] According to at least one aspect of the present disclosure, An electrophotographic member having a substrate and an elastic layer on an outer peripheral surface of the substrate, The elastic layer contains silicone rubber, The elastic layer has a tensile modulus of 0.20 MPa or less in a direction perpendicular to the thickness direction, The compressive elastic modulus of the elastic layer in the thickness direction is 0.19 to 0.57 MPa; the ratio of the tensile elastic modulus in a direction perpendicular to the thickness direction to the compressive elastic modulus in the thickness direction of the elastic layer (tensile elastic modulus / compressive elastic modulus) is 0.80 or less; A rectangular parallelepiped sample, 50 mm long, 50 mm wide and 150 μm thick, is sampled from the elastic layer and placed in an atmosphere having an oxygen concentration of 1% by volume or less and a temperature of 240° C. for 10 hours at intervals of 10 hours up to 100 hours. When the compressive moduli of the sample in a direction corresponding to the thickness direction of the elastic layer are defined as compressive moduli H0 to H100, the reduction rate of each of the compressive moduli H10 to H100 is 5% or less based on the compressive moduli H0, thereby providing an electrophotographic member. Furthermore, according to at least one aspect of the present disclosure, there is provided a heat fixing device in an electrophotographic image forming apparatus, the heat fixing device comprising a fixing member and a pressure member arranged opposite the fixing member, and at least one of the fixing member and the pressure member being the above-mentioned electrophotographic member. Furthermore, according to at least one aspect of the present disclosure, there is provided an electrophotographic image forming apparatus including the above heat fixing device. Effect of the Invention

[0008] According to at least one aspect of the present disclosure, a fixing member having low hardness and excellent durability can be obtained. Also, according to at least one aspect of the present disclosure, a heat fixing device contributing to stable formation of high-quality electrophotographic images can be obtained. Furthermore, according to at least one aspect of the present disclosure, an electrophotographic image forming apparatus capable of stably forming high-quality electrophotographic images can be obtained. [Brief description of the drawings]

[0009] [Figure 1] 2 illustrates an arrangement of thermally conductive fillers in an elastic layer of a fixing member according to one embodiment of the present disclosure. [Diagram 2] 1A and 1B are schematic cross-sectional views of fuser members according to two embodiments of the present disclosure: (a) a fuser belt, and (b) a fuser roller. [Diagram 3] 1A and 1B are an overhead view and a cross-sectional view of a corona charger. [Figure 4] 3A and 3B are diagrams illustrating a first cross section and a second cross section of an elastic layer of a belt-shaped fixing member. [Diagram 5] 4 is a schematic diagram showing a method for confirming the degree and angle of alignment of a filler in an elastic layer. FIG. [Figure 6] FIG. 2 is an explanatory diagram of a method for measuring the tensile modulus of an elastic layer according to the present disclosure. [Figure 7] FIG. 2 is a schematic cross-sectional view of an example of a heat fixing device using a heating belt and a pressure belt. [Figure 8] FIG. 2 is a schematic cross-sectional view of an example of a heat fixing device using a heating belt and a pressure roller. [Figure 9] FIG. 2 is a schematic diagram of an example of a step of laminating a surface layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In the present disclosure, the description of a numerical range such as "XX or more and YY or less" or "XX to YY" means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. In addition, in the present disclosure, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ.

[0011] The elastic layer of Patent Document 2 achieves higher thermal conductivity while suppressing an increase in hardness of the elastic layer by arranging the thermally conductive filler in the elastic layer in a specific state in the thickness direction of the elastic layer.

[0012] However, as a result of the study by the present inventors, as a result of arranging the thermally conductive filler in the thickness direction of the elastic layer, the compression hardness in the thickness direction of the elastic layer may increase compared to before the arrangement. This is considered to be because the thermal conduction path of the filler, which is a rigid body, has the effect of suppressing deformation like a tension rod when deformation in the compression direction is applied to the elastic layer. Therefore, in order to obtain an elastic layer with a lower hardness using the technology according to Patent Document 2, it is effective to reduce the tensile modulus of the silicone rubber in the elastic layer to, for example, 0.20 MPa or less.

[0013] However, when a fixing member in which the tensile modulus of the silicone rubber in the elastic layer is set to 0.20 MPa or less is used for forming electrophotographic images over a long period of time, the elastic layer may break or undergo plastic deformation. The present inventors speculate that the cause of the break or plastic deformation is as follows. The crosslinked structure of the silicone rubber in the elastic layer is broken over time, and the rubber elasticity gradually decreases, which is called the aging phenomenon. Here, it is common to configure the elastic layer so that the crosslinked structure is reconstructed by the reaction of the unsaturated aliphatic group by adjusting the H / Vi of the addition curing type liquid silicone rubber used to form the elastic layer and leaving an unsaturated aliphatic group in the silicone rubber after curing.

[0014] However, compared to the breaking of the cross-linked structure, the reconstruction of the cross-linked structure takes time. Therefore, in the elastic layer placed in a high-temperature environment, first, the hardness decreases due to the breaking of the cross-linked structure of the silicone rubber, and then the hardness that was once decreased increases due to the reconstruction of the cross-linked structure. Hereinafter, the phenomenon in which the hardness decreases prior to the reconstruction of the cross-linked structure is also called "initial decrease in hardness". Herein, if the hardness of the elastic layer before being placed in a high-temperature environment is originally low, the hardness of the elastic layer will further decrease due to the initial decrease in hardness of the elastic layer. In this way, the elastic layer whose hardness has further decreased cannot withstand the repeated compression applied to the elastic layer in the fixing process, and it is considered that breakage or plastic deformation occurs.

[0015] Therefore, the present inventors have conducted extensive research to obtain a fixing member in which the elastic layer does not break or undergo plastic deformation during use even when the hardness of the silicone rubber in the elastic layer is lowered.As a result, the inventors have found that by using an elastic layer in which the silicone rubber in the elastic layer has a lower hardness, which has been subjected to an initial hardness reduction process in advance and in which the silicone rubber in the elastic layer has undergone a transition from a process in which the crosslinked structure is predominantly broken to a process in which the crosslinked structure is predominantly reconstructed, it is possible to obtain an elastic layer that is flexible but does not break or undergo plastic deformation even when used for repeatedly forming electrophotographic images.

[0016] Specifically, such an elastic layer can be expressed as follows: a rectangular parallelepiped sample 50 mm long, 50 mm wide, and 150 μm thick is sampled from the elastic layer, and placed in an atmosphere with an oxygen concentration of 1% by volume or less and a temperature of 240°C, and when the compressive moduli of the sample in the direction corresponding to the thickness direction of the elastic layer are defined as compressive moduli H0 to H100, the rate of decrease of each of the compressive moduli H10 to H100 is 5% or less, based on the compressive moduli H0.

[0017] That is, in the heat fixing process, when the elastic layer of the fixing member is placed in an environment to which the silicone rubber in the elastic layer is exposed (an environment with a high temperature of 240°C and where the supply of oxygen is substantially cut off), and the compressive elastic modulus of the elastic layer is measured every 10 hours up to 100 hours, the elastic layer that has already undergone the initial hardness reduction process has an extremely small change in compressive elastic modulus between adjacent times, specifically, 5% or less. That is, the fixing member according to one embodiment of the present disclosure includes a substrate and an elastic layer on an outer peripheral surface of the substrate, the elastic layer containing silicone rubber, and the elastic layer has a tensile modulus of elasticity in a direction perpendicular to the thickness direction of 0.20 MPa or less and a compressive modulus of elasticity in the thickness direction of 0.19 to 0.57 MPa.

[0018] In addition, the ratio of the tensile elastic modulus in a direction perpendicular to the thickness direction to the compressive elastic modulus in the thickness direction of the elastic layer (tensile elastic modulus / compressive elastic modulus) is 0.80 or less, A rectangular parallelepiped sample having a length of 50 mm, a width of 50 mm and a thickness of 150 μm is sampled from the elastic layer, and placed in an atmosphere with an oxygen concentration of 1% by volume or less and a temperature of 240°C. When the compressive moduli of the sample in the direction corresponding to the thickness direction of the elastic layer are defined as compressive moduli H0 to H100, the rate of decrease of each of the compressive moduli H10 to H100 is 5% or less, based on the compressive moduli H0.

[0019] The tensile modulus of elasticity in the direction perpendicular to the thickness direction of the elastic layer being 0.20 MPa or less means that the silicone rubber interposed between the thermally conductive fillers in the elastic layer has low hardness.

[0020] In addition, the compressive elastic modulus of the elastic layer in the thickness direction is 0.19 to 0.57 MPa, which means that although the thermally conductive filler is arranged in the thickness direction in the elastic layer, the elastic layer as a whole is flexible. This regulation also means that the silicone rubber is interposed between the thermally conductive fillers arranged in the thickness direction of the elastic layer, and the elastic layer maintains sufficient softness even when compressed.

[0021] Furthermore, the ratio of the tensile modulus in the direction perpendicular to the thickness direction to the compressive modulus in the thickness direction of the elastic layer (tensile modulus / compressive modulus) being 0.80 or less means that the thermally conductive filler in the elastic layer is aligned in the thickness direction of the elastic layer.

[0022] A rectangular parallelepiped specimen 50 mm long, 50 mm wide, and 150 μm thick is sampled from the elastic layer and placed in an atmosphere with an oxygen concentration of 1 vol% or less and a temperature of 240°C. When the compressive moduli of the specimen in the direction corresponding to the thickness direction of the elastic layer are defined as H0 to H100 every 10 hours up to 100 hours, the decrease rate of each of the compressive moduli H10 to H100 based on the compressive modulus H0 is 5% or less, which means, as described above, that the silicone rubber in the elastic layer has already undergone an initial decrease in hardness of its crosslinked structure. An electrophotographic member according to an embodiment of the present disclosure will be described in detail below based on a specific configuration.

[0023] (1) Outline of the structure of electrophotographic components The electrophotographic member according to at least one embodiment of the present disclosure is, for example, a fixing member. The electrophotographic member may also be a pressure member such as a pressure belt or a pressure roller. Details will be described with reference to the drawings. 2(a) and (b) are schematic cross-sectional views showing the fixing member according to the present embodiment. FIG. 2(a) shows an example of the fixing member in the form of a belt, and FIG. 2(b) shows an example of the fixing member in the form of a roller. In FIG. 2(a) and (b), reference numeral 3 indicates a substrate, and reference numeral 4 indicates an elastic layer containing silicone rubber that covers the outer peripheral surface of the substrate 3. In FIG. 2, the radial direction corresponds to the thickness direction of the elastic layer.

[0024] Thus, the fixing member according to this embodiment has a base 3 and an elastic layer 4 containing silicone rubber on the base 3. As shown in these figures, the fixing member can have a surface layer 6 on the elastic layer 4 containing silicone rubber. An adhesive layer 5 may be provided between the surface layer 6, and in this case, the surface layer 6 is fixed to the outer peripheral surface of the elastic layer 4 containing silicone rubber by the adhesive layer 5. All of the fixing members shown in Fig. 2 have an endless shape. An endless shape is a shape that allows the same part to pass through the fixing nip portion multiple times (endlessly) by rotating and moving in the circumferential direction.

[0025] (2) Substrate When the fixing member is in the form of a belt as shown in FIG. 2(a), the base 3 can be made of metals such as electroformed nickel sleeves and stainless sleeves, or heat-resistant resins such as polyimide. In particular, when the thermal fixing device is of an electromagnetic induction heating type, an alloy mainly composed of nickel or iron is used from the viewpoint of heat generation efficiency. A layer for imparting a function of improving adhesion with the elastic layer can be provided on the outer surface (the surface on the elastic layer side) of the base 3. That is, the elastic layer 4 only needs to be provided on the outer peripheral surface of the base 3, and other layers can be provided between the elastic layer 4 and the base 3. In addition, a layer for imparting functions such as wear resistance and lubricity can be further provided on the inner surface (the surface opposite to the outer surface) of the base 3. In addition, when the base 3 is in the form of a belt, a core is inserted into the inside of the sleeve during the following manufacturing process.

[0026] When the fixing member is in the form of a roller as shown in Fig. 2(b), a core made of a metal such as aluminum or iron or an alloy can be used for the base 3, and it is sufficient if it has the strength to withstand the heat and pressure in the thermal fixing device. In Fig. 2(b), a solid core is used as the base 3, but a hollow core may also be used for the base 3, and a heat source such as a halogen lamp may be provided inside.

[0027] (3-1) Elastic layer The elastic layer is a layer for imparting flexibility to the electrophotographic member in order to secure a fixing nip in a thermal fixing device. When the electrophotographic member is used as a heating member that contacts toner on paper, the elastic layer also functions as a layer for imparting flexibility so that the surface of the heating member can follow the unevenness of the paper. The elastic layer includes rubber as a matrix and a thermally conductive filler dispersed in the rubber. More specifically, for example, the elastic layer includes silicone rubber and a thermally conductive filler, and is composed of a cured product obtained by curing a composition (hereinafter, silicone rubber composition) that includes at least raw materials for silicone rubber (base polymer, crosslinking agent, etc.) and a thermally conductive filler.

[0028] When the silicone rubber composition is liquid, the thermally conductive filler is easily dispersed, and the elasticity of the elastic layer to be produced is easily adjusted by adjusting the degree of crosslinking according to the type and amount of the thermally conductive filler. In addition, the silicone rubber is preferably electrically insulating or semiconductive, since the surface is charged before the electric field-oriented rubber is cured to orient the filler, as described below. For example, a silicone polymer cured as described below can be used.

[0029] The matrix has a function of exhibiting elasticity in the elastic layer. The matrix of the elastic layer according to the present embodiment contains silicone rubber from the viewpoint of exhibiting the above-mentioned function of the elastic layer. Silicone rubber has high heat resistance that can maintain flexibility even in an environment where the temperature in the non-paper passing area is as high as about 240°C, and is therefore preferable. As the silicone rubber, for example, a cured product of an addition curing type silicone rubber composition described later can be used. The silicone rubber composition typically contains the following components (a) to (d): Component (a): Linear organopolysiloxane having an unsaturated aliphatic group Component (b): Organopolysiloxane having active hydrogen bonded to silicon Component (c): Catalyst Component (d): Thermally conductive filler Each component will be described below.

[0030] Component (a): Linear organopolysiloxane having an unsaturated aliphatic group The linear organopolysiloxane having an unsaturated aliphatic group is an organopolysiloxane having an unsaturated aliphatic group such as a vinyl group, and has a structure in which siloxane bonds are connected in a linear chain. For example, the linear organopolysiloxane having an unsaturated aliphatic group may be at least one selected from the group consisting of compounds represented by the following formula (1) and compounds represented by the following formula (2). [ka] In formula (1), m 1represents an integer of 0 or more (preferably 500 to 1100), and n 1 represents an integer of 3 or more (preferably 10 to 40). 1 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group, provided that R 1 At least one of R represents a methyl group. 2 each independently represents an unsaturated aliphatic group. [ka] In formula (2), n 2 represents an integer of 1 or more (preferably 500 to 1100), R 3 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group, provided that R 3 At least one of R represents a methyl group. 4 each independently represents an unsaturated aliphatic group.

[0031] In formula (1) and formula (2), R 1 and R 3 Examples of the monovalent unsubstituted or substituted hydrocarbon group not containing an unsaturated aliphatic group that can be represented by include the following groups. Unsubstituted hydrocarbon groups Alkyl groups (eg, methyl, ethyl, propyl, butyl, pentyl, hexyl). Aryl groups (eg, phenyl groups). Substituted hydrocarbon groups Substituted alkyl groups (eg, chloromethyl, 3-chloropropyl, 3,3,3-trifluoropropyl, 3-cyanopropyl, 3-methoxypropyl).

[0032] The organopolysiloxanes represented by formula (1) and formula (2) have at least one methyl group directly bonded to a silicon atom forming a chain structure. R 1 and R 3 It is preferable that 50% or more of each group are methyl groups, and all of R1 and R 3 More preferably, is a methyl group. In addition, in formula (1) and formula (2), R 2 and R 4 Examples of the unsaturated aliphatic group that can be represented include the following groups. That is, examples of the unsaturated aliphatic group include a vinyl group, an allyl group, a 3-butenyl group, a 4-pentenyl group, and a 5-hexenyl group. Among these groups, the following are particularly preferred because they are easy to synthesize and handle, are inexpensive, and undergo crosslinking reactions easily. Since it is carried out, R 2 and R 4 is preferably a vinyl group.

[0033] From the viewpoint of moldability, the viscosity of component (a) is 1000mm 2 / s or more 20000mm 2 / s or less is preferable, and 3000 mm 2 / s or more 8000mm 2 / s or less is more preferable. 2 / s or more, it is easy to adjust the hardness required for the elastic layer, and 2 When the viscosity is less than or equal to 1 / s, the filler can be easily oriented by the electric field. The viscosity (kinetic viscosity) can be measured using a capillary viscometer, a rotational viscometer, or the like based on JIS Z 8803:2011. The blending amount of component (a) is preferably 55% by volume or more from the viewpoint of durability and 65% by volume or less from the viewpoint of heat conductivity, based on the silicone rubber composition used to form the elastic layer.

[0034] Component (b): Organopolysiloxane having active hydrogen bonded to silicon The organopolysiloxane having active silicon-bonded hydrogens functions as a crosslinker that reacts with the unsaturated aliphatic groups of component (a) in the presence of a catalyst to form a cured silicone rubber. Any organopolysiloxane having a Si-H bond can be used as component (b). In particular, from the viewpoint of reactivity with the unsaturated aliphatic group of component (a), it is preferable to use one having an average of 3 or more hydrogen atoms bonded to silicon atoms in one molecule. Specific examples of component (b) include the linear organopolysiloxane shown in the following formula (3) and the cyclic organopolysiloxane shown in the following formula (4). [ka] In formula (3), m 2 represents an integer of 0 or more (preferably 10 to 30), and n 3 represents an integer of 3 or more (preferably 5 to 20), R 5 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group. [ka] In formula (4), m 3 represents an integer of 0 or more (preferably 10 to 30), and n 4 represents an integer of 3 or more (preferably 5 to 20), R 6 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group.

[0035] R in formula (3) and formula (4) 5 and R 6 Examples of the monovalent unsubstituted or substituted hydrocarbon group not containing an unsaturated aliphatic group that can be represented by R 1 Among these, R 5 and R 6 It is preferred that 50% or more of each be a methyl group. All R 5 and R 6 More preferably, is a methyl group.

[0036] Component (c): Catalyst The catalyst used in forming the silicone rubber may be, for example, a hydrosilylation catalyst for promoting the curing reaction. As the hydrosilylation catalyst, for example, a known substance such as a platinum compound or a rhodium compound may be used. The amount of the catalyst to be added may be appropriately set and is not particularly limited.

[0037] Component (d): Thermally conductive filler The thermally conductive filler is selected taking into consideration its own thermal conductivity, specific heat capacity, density, particle size, relative dielectric constant, etc. Thermally conductive fillers used for the purpose of improving the heat transfer properties of inorganic substances, particularly metals and metal compounds, include the following: silicon carbide, silicon nitride, boron nitride, aluminum nitride, alumina, zinc oxide, magnesium oxide, silica, copper, aluminum, silver, iron, nickel, metallic silicon, and carbon fiber. From the viewpoints of the thermal conductivity, electrical resistance, and dielectric constant of the filler itself, it is more preferable that the filler is at least one type of filler selected from the group consisting of alumina, zinc oxide, metallic silicon, silicon carbide, boron nitride, and magnesium oxide. Also, from the viewpoint of the heat resistance of the elastic layer, the ionic impurities (Na + Metallic silicon and silicon carbide, which have fewer ions such as arsenic, are more preferable.

[0038] The filler may be surface-treated from the viewpoint of affinity to silicone and electrical resistance. Specifically, fillers such as alumina, silica, and magnesium oxide having active groups such as hydroxyl groups on the surface may be surface-treated with a silane coupling agent, hexamethyldisilazane, etc. Metal fillers may be surface-treated by forming an oxide film. Furthermore, the electrical resistance may be adjusted for the entire silicone rubber composition. Even if a filler has a relatively low electrical resistance, the electrical resistance of the entire composition can be adjusted by using it in combination with a second filler having a high electrical resistance. The particle size of the filler is preferably from 0.1 μm to 100 μm, and more preferably from 0.3 μm to 30 μm. The particle size here refers to the volume average particle size. From the viewpoint of reducing hardness, the filler content in the elastic layer is preferably 30 vol % or more and less than 50 vol %, and more preferably 35 vol % or more and 40 vol % or less, relative to the silicone rubber.

[0039] (3-2) Orientation of thermally conductive fillers in the elastic layer The thermally conductive filler can be oriented and aligned by the electric field application step described below. It is preferable that large particle size fillers having a circle equivalent diameter of 5 μm or more (for example, 5 to 30 μm) are not aligned as much as possible. When binary images of 150 μm×100 μm in size are obtained at any five points on the first cross section in the thickness direction and circumferential direction (thickness-circumferential direction) of the elastic layer, and binary images of 150 μm×100 μm in size are obtained at any five points on the second cross section in the thickness direction and axial direction (thickness-axial direction) of the elastic layer, the average value of the area ratio (%) of the large particle size fillers in each of the total of 10 binary images (hereinafter, also referred to as the "average area ratio of the large particle size fillers") is 20% or more and 40% or less. Here, the area ratio of the large particle size fillers means [(total area of ​​the large particle size fillers in the binary images×100) / (area of ​​the binary image)]. When the average area ratio of the large particle size filler is 20% or more, the distance between the large particle size fillers is short, a sufficiently large local electric field can be generated when an electric field is applied, and it is easy to sufficiently align the small particle size fillers present between the large particle size fillers. Also, when the average area ratio of the large particle size filler is 40% or less, it is easy to sufficiently reduce the hardness of the elastic layer.

[0040] It is preferable that the small particle size filler particles having a circle equivalent diameter of less than 5 μm are arranged. Then, the average value of the area ratio of the small particle size filler particles in each of the binarized images (hereinafter, "small particle size filler particles") is calculated. It is preferable that the average area ratio of the small particle size filler (also referred to as the "average area ratio of the small particle size filler") is 10% or more and 20% or less. Here, the area ratio of the small particle size filler refers to [(total area of ​​the small particle size filler in the binary image x 100) / (area of ​​the binary image)]. If the average area ratio of the small particle size filler is less than 10%, it is difficult to arrange the small particle size filler to achieve sufficiently high thermal conductivity. Also, if the average area ratio of the small particle size filler is more than 20%, the viscosity of the material increases, which may cause problems with the processability and smoothness of the elastic layer.

[0041] The sum of the average area ratio of the large particle size filler and the average area ratio of the small particle size filler is preferably 30% or more and 60% or less, and particularly preferably 30% or more and 50% or less. The sum of the average area ratio of the large particle size filler and the average area ratio of the small particle size filler is a value that is closely related to the volume ratio of the total filler in the elastic layer. By setting the sum of the average area ratio of the large particle size filler and the average area ratio of the small particle size filler within the above range, it is possible to better achieve both high thermal conductivity of the elastic layer and suppression of high hardness.

[0042] (3-3) Confirmation of the arrangement of thermally conductive fillers in the elastic layer The arrangement state of the thermally conductive filler can be confirmed by performing a two-dimensional Fourier transform using a binarized image obtained from a cross-sectional image of the elastic layer. Specifically, the procedure is as follows. First, a measurement sample is prepared. For example, when the fixing member is a fixing belt 400 as shown in FIG. 4(a), as shown in FIG. 4(b), for example, 10 samples 401 each having a length of 5 mm, a width of 5 mm, and a thickness equal to the total thickness of the fixing belt are taken from 10 arbitrary positions of the fixing belt. For five of the obtained 10 samples, a cross section in the circumferential direction of the fixing belt, that is, a cross section including a first cross section 401-1 in the thickness-circumferential direction of the elastic layer, is polished using an ion beam. For the remaining five samples, a cross section in a direction perpendicular to the circumferential direction of the fixing belt, that is, a cross section including a second cross section 401-2 in the thickness-axial direction of the elastic layer, is polished using an ion beam. A cross-section polisher is used for polishing the cross section with an ion beam. In polishing the cross section with an ion beam, it is possible to prevent the filler from falling off the sample and the abrasive from being mixed in, and it is also possible to form a cross section with few polishing marks.

[0043] Next, for five samples in which the first cross section of the elastic layer was polished, and for five samples in which the second cross section of the elastic layer was polished, the first cross section and the second cross section of the elastic layer were observed using a laser microscope or a scanning electron microscope (SEM), and cross-sectional images of an area of ​​150 μm x 100 μm were obtained (Figure 5(a)). Next, the obtained image is binarized using commercially available image software so that the filler part is white and the silicone rubber part is black (Figure 5B). The Otsu method is used for binarization. Next, the circle equivalent diameter is calculated for each filler 7, 8 in the obtained binarized image, and the image is divided into an image in which only large particle size fillers 7 with a circle equivalent diameter of 5 μm or more remain (FIG. 5(c)), and an image in which only small particle size fillers 8 with a circle equivalent diameter of less than 5 μm remain (FIG. 5(d)). Then, the area ratio of the large particle size fillers 7 and the small particle size fillers 8 (the ratio of the total area of ​​each filler 7, 8 to the total area of ​​the image) is calculated from each image. The circle equivalent diameter of each filler refers to the diameter of a circle having the same area as the area of ​​the filler.

[0044] Furthermore, by performing two-dimensional Fourier transform analysis on the large particle size filler image and the small particle size filler image, an elliptical plot diagram showing the direction and degree of filler arrangement can be obtained (Fig. 5(e) and Fig. 5(f) respectively). Because the two-dimensional Fourier transform itself has a peak in the direction perpendicular to the periodicity of the binary image, the elliptical plot diagram is the result of shifting the phase of the two-dimensional Fourier transform result by 90°. The arrangement angle Φ can be calculated from the angle made by the semi-major axis of this elliptical plot diagram, and the filler arrangement degree f, defined as f=1-(y / x) when the semi-major axis is x and the semi-minor axis is y, can be calculated. The arrangement angle Φ represents the arrangement direction of the filler, and in Figures 5(e) and 5(f), the 90°-270° direction represents the thickness direction of the elastic layer, and the 0°-180° direction represents the circumferential direction or axial direction of the elastic layer. Therefore, the closer the arrangement angle Φ is to 90°, the more the filler is arranged in the thickness direction. Additionally, the degree of alignment f represents the flattening of the ellipse and is a value between 0 and 1. When f is 0, it becomes a circle, representing a completely random state with no alignment, and as f approaches 1, the flattening of the ellipse becomes greater, and the degree of alignment of the filler also increases. The filler arrangement angle Φ and the degree of arrangement f are calculated as the average values ​​of 10 locations in total, 5 locations on each of the first cross section in the thickness-circumferential direction of the elastic layer and the second cross section in the thickness-axial direction.

[0045] In this embodiment, the average area ratio of large-particle-size fillers having a particle size (circle-equivalent diameter) of 5 μm or more is preferably 20% or more and 40% or less, and more preferably 30% or more and 35% or less. When the average area ratio of large-particle-size fillers is 20% or more, the interparticle distance between the large-particle-size fillers is short, and it is easy to generate a sufficient local electric field. Therefore, the small-particle-size fillers present between the large-particle-size fillers can be sufficiently arranged, and it is easier to achieve high thermal conductivity. In addition, when the average area ratio of large-particle-size fillers is 40% or less, it is easy to sufficiently reduce the hardness of the elastic layer.

[0046] If the average degree of alignment of the large particle size filler is fL, fL is 0.00 or more and 0.15 or less. It is preferable that fL is 0.10 or more and 0.15 or less, and more preferable that fL is 0.15 or less. By making fL 0.15 or less, it is possible to achieve a low hardness of the elastic layer. When the average arrangement angle of the large particle size filler is ΦL, ΦL may be any value between 0° and 180°. The average area ratio of small particle size fillers with particle size of less than 5 μm is preferably 10% or more and 20% or less, more preferably 10% or more and 15% or less. When the average area ratio of small particle size fillers is 10% or more, sufficiently high thermal conductivity can be achieved. Also, when the average area ratio of small particle size fillers is 20% or less, problems in processability and smoothness caused by an increase in the viscosity of the material can be prevented.

[0047] When the average arrangement angle of the small particle size filler is ΦS, ΦS is preferably 60° or more and 120° or less, and more preferably 80° or more and 100° or less. The direction where ΦS is 90° is the thickness direction of the elastic layer, so the closer ΦS is to 90°, the more it is arranged in the thickness direction. Therefore, by having ΦS in the above range, the thermal conductivity in the thickness direction can be improved. Here, 30° and 150° are in a mirror image relationship with 90° as the boundary, so they are synonymous in terms of heat transfer function in the thickness direction.

[0048] (3-4) Step of applying an electric field to the elastic layer The corona charger 2 and the process of applying an electric field to the elastic layer using the corona charger will be described below as one embodiment. Corona charging methods include the scorotron method, which has a grid electrode between the corona wire and the body to be charged, and the corotron method, which does not have a grid electrode. From the viewpoint of controllability of the surface potential of the body to be charged, the scorotron method is preferred. 3(a) and (b), the corona charger 2 includes a front block 201, a rear block 202, and shields 203 and 204. A discharge wire 205 is stretched between the front block 201 and the rear block 202. When a charging bias is applied from a high-voltage power supply, the discharge wire 205 discharges and charges the surface of the uncured elastic layer 4 on the substrate as the body to be charged. Similar to the configuration of a general corona charger, a high voltage is applied to a discharge wire 205 as a discharge member. The ion flow obtained by discharge to the shields 203 and 204 is controlled by applying a high voltage to the grid 206, and the surface of the elastic layer 4 is controlled to a desired charged potential. At this time, since the base 3 or the core 1 holding the base 3 is grounded (not shown), a desired electric field is generated in the elastic layer 4 by controlling the surface potential of the elastic layer 4. It is possible to revive it.

[0049] The manufacturing method of the fixing member of the embodiment will be described in detail. First, an elastic layer having silicone rubber containing a thermally conductive filler is formed on a substrate. Next, as shown in FIG. 3(a), a corona charger 2 is arranged to face closely along the width direction of the elastic layer 4 of the fixing member 100 before hardening. Then, a voltage is applied to the grid 206 of the corona charger 2, and the fixing member 100 is rotated at 141 rpm for 160 seconds in a discharged state, thereby charging the surface of the elastic layer. The distance between the surface of the elastic layer and the grid 206 can be 1 mm to 10 mm. By charging the surface of the elastic layer 4 in this way, an electric field is generated in the elastic layer, and the thermally conductive filler is oriented. After that, the elastic layer is hardened by heating or the like, and the orientation of the filler is fixed.

[0050] The voltage applied to the grid 206 is preferably in the range of 0.1 kV to 3 kV (0.2 to 6 kV in Vp-p in the case of AC application) in terms of generating an effective electrostatic interaction in the filler. When forming the filler orientation in the thickness direction of the elastic layer using an electric field, it is important to generate an electric field in the thickness direction of the elastic layer 4. If the sign of the applied voltage is equal to the sign of the voltage applied to the wire, the direction of the electric field will be reversed whether it is negative or positive, but the effect obtained is the same. In addition, when AC charging is performed to suppress the liquid surface flow described later, it is desirable to match the phase of the waveform of the wire and the grid. Depending on the type of thermally conductive filler, it may be difficult to form the orientation of the amorphous filler, in which case it is desirable to increase the voltage applied to the grid 206. It is presumed that this is related to the dielectric constant of the silicone rubber component and the thermally conductive filler. When the dielectric constant difference between the silicone rubber and the filler is large, it is possible to form the orientation of the amorphous filler with a relatively small applied voltage. On the other hand, if the voltage applied to the grid 206 is too large, the electrostatic repulsive force due to the surface charge of the elastic layer becomes large, causing the liquid surface to flow, which may deteriorate the surface properties of the elastic layer 4. Therefore, the voltage applied to the grid 206 is more preferably in the range of 0.1 kV to 1.5 kV in absolute value (1.2 to 3 kV in Vp-p in the case of AC application). This liquid surface flow can be alleviated by applying AC charging.

[0051] As a configuration for controlling the electric potential in the longitudinal direction of the elastic layer surface, for example, the configuration shown in Fig. 3(a) can be used, and while a voltage is applied to the grid 206, the entire elastic layer 4 can be charged by rotating the fixing belt 11 around the central axis of the fixing belt 11 as the rotation axis. It is preferable that the rotation speed of the fixing belt is 10 rpm to 500 rpm, and that the treatment time is 20 seconds or more from the viewpoint of stably forming the orientation of the filler. As described above, the formation of the orientation of the irregular filler can be controlled by controlling the surface potential and the time for applying the electric field.

[0052] The corona charger uses a reciprocating mechanism to vibrate the fixing member back and forth at about ±1 to 10 mm in the longitudinal direction and at about 1 to 10 Hz, thereby suppressing sudden changes in thermal conductivity, surface properties, and hardness at the boundary between areas where an electric field is applied and areas where it is not applied. Although stainless steel, nickel, molybdenum, tungsten, etc. may be used as the discharge wire 205, it is preferable to use tungsten, which is a very stable metal. The discharge wire stretched inside the shield may have a circular cross section or a sawtooth cross section. The diameter of the discharge wire 205 is preferably 40 μm to 100 μm. By setting the diameter of the discharge wire within this range, it is possible to prevent the discharge wire from being cut by ions during discharge, and it is also possible to eliminate the need to make the voltage required to generate a corona discharge excessively high. Either a DC voltage or an AC voltage can be used as the voltage applied to the discharge wire 205. In the case of an AC voltage, the frequency should be 0.01 Hz to 1000 Hz. It is preferable to perform the measurement at about z. The voltage can be generated by outputting a square wave, sine wave, or the like using an arbitrary waveform generator.

[0053] (3-5) Adjusting the elastic modulus of silicone rubber In the elastic layer of the present disclosure, it is preferable to orient the filler in the thickness direction in the above-mentioned process in order to achieve high thermal conductivity. When the filler is oriented, the compressive elastic modulus (hardness) in the thickness direction is higher than when the filler is not oriented, and anisotropy occurs with the tensile elastic modulus in the direction perpendicular to the thickness direction. In order to increase the thermal conductivity in the thickness direction of the elastic layer, the thermally conductive filler is arranged in the thickness direction of the elastic layer, so that the ratio of the tensile modulus in the direction perpendicular to the thickness direction to the compressive modulus in the thickness direction of the elastic layer (tensile modulus / compressive modulus) can be 0.80 or less. The lower limit of the ratio is not particularly limited, but is, for example, 0.10 or more. The ratio is preferably 0.10 to 0.55, more preferably 0.10 to 0.40. The "tensile modulus / compressive modulus" value of the elastic layer as described above indicates that there is anisotropy between the compressive modulus in the thickness direction and the tensile modulus in the direction perpendicular to the thickness direction. This indicates that the compressive modulus is relatively hard due to the arrangement of the filler compared to the flexibility of the silicone rubber in the elastic layer, and can be an index showing the degree of alignment of the filler in the elastic layer as a whole. The value of the above ratio can be adjusted, for example, by adjusting the degree of crosslinking of the silicone rubber and / or by controlling the degree of alignment of the filler in the above-mentioned electric field application step when forming the elastic layer.

[0054] On the other hand, an increase in the elastic modulus in the compression direction reduces the ability of the material to conform to the unevenness of the paper fibers, so to offset the increase in elastic modulus, the elastic modulus (degree of cross-linking) of the silicone rubber (polymer) excluding the filler is reduced, and the compressive elastic modulus of the entire elastic layer is set to be within the range of 0.19 to 0.57 MPa. Here, the degree of crosslinking of the silicone rubber in the elastic layer, that is, the elastic modulus of the silicone rubber, is one index of the tensile modulus in the direction perpendicular to the thickness direction of the elastic layer. That is, the compressive elastic modulus of the elastic layer is influenced not only by the elastic modulus of the silicone rubber in the elastic layer, but also by the arrangement state of the thermally conductive filler. On the other hand, the tensile modulus in the direction perpendicular to the thickness direction of the elastic layer is determined by the silicone rubber in the elastic layer. In the elastic layer according to the present disclosure, the tensile modulus in the direction perpendicular to the thickness direction is 0.20 MPa or less, preferably 0.19 MPa or less, and further 0.18 MPa or less. The lower limit is not particularly limited, but from the viewpoint of maintaining the strength as the elastic layer, it is preferably 0.01 MPa or more, particularly 0.10 MPa or more. The preferred range of the tensile modulus is 0.01 to 0.20 MPa, particularly 0.10 to 0.20 MPa, and further 0.10 to 0.19 MPa. By setting the tensile modulus of elasticity in the direction perpendicular to the thickness direction of the elastic layer to 0.20 MPa or less, even if the thermally conductive filler in the elastic layer is arranged in the thickness direction, the compressive modulus of elasticity of the entire elastic layer can be set in the above-mentioned range of 0.19 to 0.57 MPa. Note that, when the electrophotographic member according to the present disclosure is, for example, an electrophotographic belt having an endless shape or an electrophotographic roller having a roller shape, the direction perpendicular to the thickness direction of the elastic layer (arrow 603 in FIG. 6(a)) may be the circumferential direction of the electrophotographic belt or electrophotographic roller, or may be the direction perpendicular to the circumferential direction, i.e., the direction along the rotation axis. In order to set the tensile modulus in the direction perpendicular to the thickness direction of the elastic layer within the above range, it is effective to increase the molecular weight of component (a) to increase the distance between crosslinking points, or to adjust the amount of component (b) added so as not to make the crosslink density too high. Specifically, the molar ratio of Si-H in component (b) to the unsaturated aliphatic group in component (a) (H / V It is desirable that i) is 0.5 or less and the toluene extraction rate is about 30 to 45%. In addition, a rectangular parallelepiped sample having a length of 50 mm, a width of 50 mm, and a thickness of 150 μm was sampled from the elastic layer according to this embodiment in an atmosphere having an oxygen concentration of 1% by volume or less and a temperature of 240° C. When the sample is left in the same position for 100 hours and the compressive elastic modulus in the thickness direction of the sample is measured three times every 10 hours, the average values ​​of which are H10 to H100, the compressive elastic modulus at time 0, H0, is taken as the standard and each of the compressive elastic moduli H10 to H100 has a decrease rate of 5% or less. A decrease rate of 5% or less for each of H10 to H100 means that the elastic layer is unlikely to soften and deteriorate over a long period of time throughout durability.

[0055] The molecular weight of the silicone rubber is preferably Mw 60,000 to 100,000. If Mw is 60,000 or more, the elastic modulus is low, and if Mw is 100,000 or less, the viscosity of the polymer does not become too high during electric field orientation, making it easier to orient the filler. The swelling ratio measured by a toluene extraction test is known as a method for indirectly measuring the crosslink density of silicone rubber, and it is desirable for the swelling ratio calculated by the following formula to be between 900% and 1200%. Swelling ratio (%) = (Wtol-Wf) / (Wdry-Wf) Wtol: weight of sample containing toluene after immersion in toluene Wf: weight of filler in sample Wdry: weight of sample after immersion in toluene and drying to remove toluene If the swelling ratio is less than 900%, it is difficult to achieve an elastic modulus of 0.20 MPa or less, and if it is more than 1200%, it becomes too flexible and the moldability decreases. By adjusting the elastic modulus within the above range, the elastic layer can exhibit low flexibility with a tensile modulus of 0.20 MPa or less.

[0056] (3-6) Measures against softening and deterioration of the elastic layer One method for making the elastic layer less susceptible to softening and deterioration over the long term through durability is to further bake the elastic layer at a high temperature after hardening, advance the oxidation and condensation reaction of the methyl groups in advance, and form a branched organopolysiloxane structure. The details are described below.

[0057] After curing, the elastic layer is further baked at a high temperature to advance the oxidation and condensation reaction of the methyl groups in advance, forming a branched organopolysiloxane structure. The cured elastic layer is heated in an oxygen-free state at a high temperature of 280°C to 350°C, more preferably at a temperature of 300°C to 350°C, to promote the oxidation and condensation of the methyl groups shown in the following reaction formula (5) and the oxidation and cracking reaction of the methyl groups shown in the following reaction formula (6). The heating time is, for example, 1 to 10 minutes. [ka] [ka] By heating to high temperatures in a low oxygen concentration state, the elastic layer undergoes oxidation and cracking of the methyl groups. The softening reaction by oxidation and condensation and the hardening reaction by oxidation and condensation proceed simultaneously. When the softening reaction and hardening reaction have progressed to a certain extent, the hardness remains stable at the same hardness as before high-temperature heating, and it is thought that the material will not soften or deteriorate easily. After the above changes have progressed, a branched organosiloxane structure is formed as shown in reaction formula (5). The branched organosiloxane structure contains three Si-O bonds per Si atom, which have higher bond energy than the Si-CC-Si bonds at the crosslinking points and the Si-C bonds with the side-chain methyl groups, and is stable against thermal and mechanical loads.

[0058] The criteria for this state are that the ratio of T units (three O bonds to Si atoms) to D units (two O bonds to Si atoms) in the siloxane bonds in the silicone rubber (T units / D units) is 0.030 or more, and that the total amount of hexamethylcyclotrisiloxane (D3), octamethylcyclotetrasiloxane (D4) and decamethylcyclopentasiloxane (D5) generated when the silicone rubber is heated at 150°C for 1 hour is 1.5 ppm or more. If any of these conditions are met, there will be less change in hardness during subsequent use, which is more preferable. Here, the former indicates that the silicone rubber has fully progressed in its hardening reaction and is stable, and the latter indicates that the silicone rubber has fully progressed in its softening reaction and is stable. The ratio of T units to D units is preferably 0.030 to 0.100, and more preferably 0.030 to 0.060. The total amount of cyclic siloxanes D3 to D5 generated is preferably 1.5 to 10 ppm, and more preferably 2.0 to 5.0 ppm.

[0059] The ratio of T units (three O bonds to a Si atom) to D units (two O bonds to a Si atom) in the siloxane bonds in the silicone rubber in the elastic layer was determined by nuclear magnetic resonance analysis ( 29 The calculation is performed by measurement using a Si-NMR (product name: JEOL JNM-ECA400; manufactured by JEOL Ltd.). Samples were taken by cutting with a blade near the interface between the base layer and the elastic layer of the fixing member and near the interface between the elastic layer and the surface layer, and isolating them from the elastic layer. The ratio of the integral value of the peak (55-60 ppm) corresponding to the T unit to the integral value of the peak (up to 25 ppm) corresponding to the D unit is quantitatively calculated. The measurement is performed using the DDMAS method, with the number of integrations set to 1000.

[0060] In addition, the amount of cyclic siloxanes generated when silicone rubber is heated at 150°C for 1 hour using headspace gas chromatography mass spectrometry (HS-GC / MS) is calculated by integrating the integral value of the retention time (RT) of cyclic siloxanes D3, D4, and D5 relative to the integral value measured when toluene is used as a standard substance at a specified concentration. A TurboMatrix HS40 Clarus 690 GC (manufactured by PerkinElmer) was used, and the measurement conditions were HS temperature 150° C. for 1 h, GC 40 to 300° C. (52 min), and MS: 35 to 500 Da.

[0061] (4) Adhesive layer of fixing member As shown in FIG. 2, the adhesive layer 5 is a layer formed by adhering the elastic layer 4 and the surface layer (release layer) 6 with, for example, an addition-curing silicone rubber adhesive. As the adhesive, it is preferable to use an addition-curing silicone rubber containing a self-adhesive component. Specifically, it contains an organopolysiloxane having a plurality of unsaturated aliphatic groups, typically vinyl groups, in the molecular chain, a hydrogenorganopolysiloxane, and a platinum compound as a crosslinking catalyst. It is then cured by an addition reaction. As such an adhesive, a known adhesive can be used.

[0062] Examples of self-adhesive components include: Alkenyl groups such as vinyl groups, (meth)acryloxy groups, hydrosilyl groups (SiH groups), a silane having at least one functional group, preferably two or more functional groups, selected from the group consisting of an epoxy group, an alkoxysilyl group, a carbonyl group, and a phenyl group; Organosilicon compounds such as cyclic or linear siloxanes having 2 to 30 silicon atoms, preferably 4 to 20 silicon atoms; A non-silicon-based (i.e., silicon-free) organic compound that may contain oxygen atoms in the molecule, provided that it contains 1 to 4, preferably 1 to 2, aromatic rings such as phenylene structures having a valence of 1 to 4, preferably valence of 2 to 4, in one molecule, and at least 1, preferably 2 to 4, functional groups capable of contributing to a hydrosilylation addition reaction (e.g., alkenyl groups, (meth)acryloxy groups) in one molecule.

[0063] The above self-adhesive components may be used alone or in combination of two or more. From the viewpoint of adjusting the viscosity and ensuring heat resistance, a filler component may be added to the adhesive within the scope of the present disclosure. Examples of the filler component include the following. Silica, alumina, iron oxide, titanium oxide, cerium oxide, cerium hydroxide, carbon black, etc. Such addition curing type silicone rubber adhesives are commercially available and are easily available. The thickness of the adhesive layer is preferably 20 μm or less. By setting the thickness to 20 μm or less, the thermal resistance of the fixing member can be set small, and the heat from the inner surface side (base side) can be efficiently transferred to the recording material (recording medium).

[0064] (5) Surface layer of fixing material The surface layer 6 is made of a fluororesin, and a tube method or a coating method is used as a molding method. The following describes the tube method, in which a resin exemplified below is molded into a tube shape and coated. Tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer (PFA), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), etc. Among the resin materials listed above, PFA is preferred from the viewpoints of moldability and toner releasability.

[0065] The thickness of the fluororesin layer (surface layer) is preferably 10 μm or more and 50 μm or less, because this maintains the elasticity of the lower elastic layer when laminated, and can ensure abrasion resistance while preventing the surface hardness as a fixing member from becoming too high. The inner surface of the fluororesin tube can be preliminarily treated with sodium, excimer laser, ammonia, or the like to improve the adhesiveness. 9 is a schematic diagram of an example of a process for laminating a surface layer 6 via an addition-curing silicone rubber adhesive on an elastic layer 4 containing silicone rubber. An addition-curing silicone rubber adhesive 5 is applied to the surface of the elastic layer 4 formed on the outer circumferential surface of a substrate 3. Furthermore, a fluororesin tube 6 as the surface layer 6 is coated on the outer surface of the adhesive 5 and laminated.

[0066] The method for covering the fluororesin tube is not particularly limited, but may be a method of covering with an addition-curing silicone rubber adhesive as a lubricant, or a method of expanding and covering the fluororesin tube from the outside. The excess addition-curing silicone rubber adhesive 5 remaining between the elastic layer and the surface layer 6 made of fluororesin 4 is removed by squeezing it out using a means not shown. From the viewpoint of heat transfer, it is preferable that the thickness of the adhesive layer 5 after being squeezed out is 20 μm or less. Next, the addition curing silicone rubber adhesive 5 is cured and adhered by heating for a predetermined time in a heating means such as an electric furnace, and both ends in the width direction are cut to the desired length to obtain the fixing member.

[0067] (6) Heat fixing device The thermal fixing device according to the present embodiment is configured so that a pair of heated rollers, belts, or other rotating bodies are pressed against each other. The type of thermal fixing device is appropriately selected in consideration of the overall process speed, size, and other conditions of the image forming apparatus in which the thermal fixing device is mounted. In a thermal fixing device, a fixing nip N is formed by pressing a heated fixing member and a pressure member, and a recording medium S, which is a heated body and has an image formed with unfixed toner, is sandwiched and conveyed through this fixing nip N. The image formed with the unfixed toner is called a toner image t. In this way, the toner image t is heated and pressurized. As a result, the toner image t is melted and mixed, and then cooled to fix the image on the recording medium. A specific example of the thermal fixing device will be given below to explain its configuration, but the scope and applications of the present invention are not limited to this example.

[0068] (6-1) Fixing belt-pressure belt type heat fixing device FIG. 7 is a schematic cross-sectional view of an example of a thermal fixing device of the so-called twin-belt type, in which a pair of rotating bodies, namely a fixing belt 11 and a pressure belt 12, are pressed against each other, the thermal fixing device having a fixing belt as a fixing member and a pressure belt as a pressure member. It should be noted that the width direction of the thermal fixing device or the components that make it up is the direction perpendicular to the plane of the paper in Figure 7. The front of the thermal fixing device is the side on which the recording medium S is introduced. Left and right are left and right when viewed from the front of the device. The belt width is the belt dimension in the left-right direction when viewed from the front of the device. The width of the recording medium S is the dimension of the recording medium in a direction perpendicular to the transport direction. Additionally, upstream and downstream are upstream and downstream in relation to the transport direction of the recording medium.

[0069] This thermal fixing device includes a fixing belt 11 as a fixing member and a pressure member as a pressure member, a pressure belt 12. The fixing belt 11 and the pressure belt 12 are each a fixing belt including a flexible base made of a metal mainly composed of nickel, as shown in Fig. 2(a), stretched over two rollers. The heating means for the fixing belt 11 is a heating source (induction heating member, excitation coil) that can use electromagnetic induction heating with high energy efficiency. The induction heating member 13 is composed of an induction coil 13a, an excitation core 13b, and a coil holder 13c that holds them. The induction coil 13a uses a Litz wire that is wound flat in an oval shape, and is placed inside a horizontal E-shaped excitation core 13b that protrudes from the center and both sides of the induction coil. The excitation core 13b uses a material with high magnetic permeability and low residual magnetic velocity density, such as ferrite or permalloy, so that loss in the induction coil 13a and excitation core 13b can be suppressed, and the fixing belt 11 can be heated efficiently.

[0070] When a high-frequency current is applied from the excitation circuit 14 to the induction coil 13a of the induction heating member 13, the base of the fixing belt 11 is inductively heated, and the fixing belt 11 is heated from the base side. The surface temperature of the fixing belt 11 is detected by a temperature detection element 15 such as a thermistor. A signal related to the temperature of the fixing belt 11 detected by this temperature detection element 15 is sent to a control circuit unit 16. The control circuit unit 16 controls the power supplied from the excitation circuit 14 to the induction coil 13a so that the temperature information received from the temperature detection element 15 is maintained at a predetermined fixing temperature, thereby adjusting the temperature of the fixing belt 11 to the predetermined fixing temperature.

[0071] The fixing belt 11 is stretched around a roller 17 as a belt rotating member and a heating side roller 18. The roller 17 and the heating side roller 18 are supported by bearings between left and right side plates (not shown) of the device so as to be freely rotatable. The roller 17 is, for example, a hollow iron roller having an outer diameter of 20 mm, an inner diameter of 18 mm, and a thickness of 1 mm, and functions as a tension roller that applies tension to the fixing belt 11. The heating side roller 18 is, for example, a highly slidable elastic roller having an outer diameter of 20 mm, a core metal made of an iron alloy having a diameter of 18 mm, and a silicone rubber layer as an elastic layer provided thereon.

[0072] This heating side roller 18, as a drive roller, receives a driving force from a drive source (motor) M via a drive gear train (not shown), and is driven to rotate in the clockwise direction of the arrow at a predetermined speed. By providing this heating side roller 18 with an elastic layer as described above, the driving force input to the heating side roller 18 can be effectively transmitted to the fixing belt 11, and a fixing nip can be formed to ensure separation of the recording medium from the fixing belt 11. By providing the heating side roller 18 with an elastic layer, heat conduction to the heating side roller is also reduced, which is also effective in shortening the warm-up time. When the heating side roller 18 is driven to rotate, the fixing belt 11 rotates together with the roller 17 due to friction between the silicone rubber surface of the heating side roller 18 and the inner surface of the fixing belt 11. The arrangement and size of the roller 17 and the heating side roller 18 are selected according to the size of the fixing belt 11. For example, the dimensions of the roller 17 and the heating side roller 18 are selected so that the fixing belt 11, which has an inner diameter of 55 mm when not installed, can be stretched over them.

[0073] The pressure belt 12 is tensioned by a tension roller 19 and a pressure side roller 20, which serve as belt rotation members. The inner diameter of the pressure belt when not attached is, for example, 55 mm. The tension roller 19 and the pressure side roller 20 are supported by bearings that are freely rotatable between the left and right side plates (not shown) of the device. The tension roller 19 is, for example, an iron alloy core having an outer diameter of 20 mm and a diameter of 16 mm, and is provided with a silicone sponge layer to reduce heat conduction from the pressure belt 12 by reducing thermal conductivity. The pressure side roller 20 is, for example, a low-sliding rigid roller made of an iron alloy having an outer diameter of 20 mm, an inner diameter of 16 mm, and a thickness of 2 mm. The dimensions of the tension roller 19 and the pressure side roller 20 are also selected according to the dimensions of the pressure belt 12. Here, in order to form a nip portion N between the fixing belt 11 and the pressure belt 12, the pressure side roller 20 is pressed toward the heating side roller 18 with a predetermined pressure force in the direction of arrow F by a pressure mechanism not shown in the figure at both left and right ends of the rotating shaft.

[0074] In addition, a pressure pad is used to obtain a wide nip portion N without enlarging the size of the device. That is, a fixing pad 21 is a first pressure pad that presses the fixing belt 11 toward the pressure belt 12, and a pressure pad 22 is a second pressure pad that presses the pressure belt 12 toward the fixing belt 11. The fixing pad 21 and the pressure pad 22 are supported and disposed between left and right side plates (not shown) of the device. The pressure pad 22 is pressed toward the fixing pad 21 with a predetermined pressure force by a pressing mechanism (not shown) in the direction of the arrow G. The fixing pad 21, which is the first pressure pad, has a pad base and a sliding sheet (low friction sheet) 23 that contacts the belt. The pressure pad 22, which is the second pressure pad, also has a pad base and a sliding sheet 24 that contacts the belt. This is because there is a problem that the portion of the pad that rubs against the inner circumferential surface of the belt is worn down significantly. By interposing the sliding sheets 23 and 24 between the belt and the pad base, wear on the pad can be prevented and sliding resistance can be reduced, ensuring good belt running performance and durability. The fixing belt is provided with a non-contact static electricity removing brush (not shown), and the pressure belt is provided with a contact static electricity removing brush (not shown).

[0075] The control circuit section 16 drives the motor M at least when image formation is being performed. This causes the heating side roller 18 to rotate, and the fixing belt 11 to rotate in the same direction. The pressure belt 12 rotates following the fixing belt 11. Here, the most downstream portion of the fixing nip is configured so that the fixing belt 11 and the pressure belt 12 are sandwiched between the roller pair 18, 20 and transported, thereby preventing the belts from slipping. The most downstream portion of the fixing nip is the fixing nip. This is the portion where the pressure distribution (in the recording medium conveying direction) is maximum. When the fixing belt 11 is heated to a predetermined fixing temperature and maintained at that temperature (called temperature control), the recording medium S having the unfixed toner image t is conveyed to the nip portion N between the fixing belt 11 and the pressure belt 12. The recording medium S is introduced with the surface carrying the unfixed toner image t facing the fixing belt 11. Then, the unfixed toner image t of the recording medium S is conveyed while being sandwiched and conveyed while being in close contact with the outer peripheral surface of the fixing belt 11, so that heat is applied from the fixing belt 11 and the unfixed toner image t is fixed to the surface of the recording medium S by receiving a pressure force. At this time, the heat from the heated base of the fixing belt 11 is efficiently transported to the recording medium S through an elastic layer having high thermal conductivity in the thickness direction. After that, the recording medium S is separated from the fixing belt by a separating member 25 and conveyed.

[0076] (6-2) Fixing belt-pressure roller type thermal fixing device Fig. 8 is a schematic diagram showing an example of a fixing belt-pressure roller type thermal fixing device using a ceramic heater as a heating body. In Fig. 8, 11 is a cylindrical or endless fixing belt, and the one described above is used. There is a heat-resistant and heat-insulating belt guide 30 for holding this fixing belt 11, and a ceramic heater 31 for heating the fixing belt 11 is fitted into a groove formed along the longitudinal direction of the guide at a position where it comes into contact with the fixing belt 11 (almost at the center of the lower surface of the belt guide 30) and fixedly supported. The fixing belt 11 is loosely fitted around the belt guide 30. A pressure rigid stay 32 is inserted inside the belt guide 30. On the other hand, a pressure roller 33 is disposed facing the fixing belt 11. In this example, the pressure roller is an elastic pressure roller, that is, a core metal 33a is provided with an elastic layer 33b of silicone rubber to reduce hardness, and both ends of the core metal 33a are rotatably supported by bearings between the front and rear chassis side plates (not shown) of the device. The elastic pressure roller is covered with a PFA (tetrafluoroethylene / perfluoroalkyl ether copolymer) tube to improve surface properties. Pressure springs (not shown) are respectively compressed between both ends of the pressure rigid stay 32 and spring bearing members (not shown) on the device chassis side, so that a downward force acts on the pressure rigid stay 32. As a result, the lower surface of the ceramic heater 31 disposed on the lower surface of the heat-resistant resin belt guide member 30 and the upper surface of the pressure roller 33 are in pressure contact with each other with the fixing belt 11 sandwiched therebetween, forming a fixing nip portion N.

[0077] The pressure roller 33 is driven to rotate counterclockwise as indicated by an arrow by a driving means (not shown). A rotational force acts on the fixing belt 11 due to friction between the outer surfaces of the pressure roller 33 and the fixing belt 11 caused by the rotational drive of the pressure roller 33, and the fixing belt 11 rotates clockwise as indicated by an arrow around the outside of the belt guide 30 at a peripheral speed substantially corresponding to the rotational peripheral speed of the pressure roller 33 while its inner surface slides in close contact with the lower surface of the ceramic heater 31 at the fixing nip portion N (pressure roller drive method). The pressure roller 33 starts to rotate based on a print start signal, and the ceramic heater 31 starts to heat up. At the moment when the rotational circumferential speed of the fixing belt 11 due to the rotation of the pressure roller 33 becomes steady and the temperature of the temperature detection element 34 provided on the upper surface of the ceramic heater rises to a predetermined temperature, for example, 180° C., the recording medium S carrying the unfixed toner image t as the heated material is introduced between the fixing belt 11 and the pressure roller 33 in the fixing nip portion N with the toner image carrying surface side facing the fixing belt 11. Then, the recording medium S is in close contact with the lower surface of the ceramic heater 31 via the fixing belt 11 in the fixing nip portion N, and moves through the fixing nip portion N together with the fixing belt 11. During the movement and passing process, the heat of the fixing belt 11 is applied to the recording medium S, and the toner image t is heated and fixed on the surface of the recording medium S. The recording medium S that has passed through the fixing nip portion N is separated from the outer surface of the fixing belt 11 and conveyed.

[0078] The ceramic heater 31 as the heating element is arranged in the direction perpendicular to the moving direction of the fixing belt 11 and the recording medium S. It is a horizontally elongated linear heating element with a low heat capacity, with the longitudinal direction being the direction in which the heater substrate 31 intersects the substrate. The basic configuration is preferably a heater substrate 31a made of aluminum nitride or the like, a heat generation layer 31b provided on the surface of the heater substrate 31a along its longitudinal direction, the heat generation layer 31b being provided by applying an electric resistance material such as Ag / Pd (silver / palladium) to a thickness of about 10 μm and a width of 1 to 5 mm by screen printing or the like, and a protective layer 31c made of glass, fluororesin or the like provided thereon. However, the ceramic heater used is not limited to this. When electricity is applied between both ends of the heat generating layer 31b of the ceramic heater 31, the heat generating layer 31b generates heat, and the temperature of the heater 31 rises rapidly. The ceramic heater 31 is fixedly supported by being fitted, with the protective layer 31c side facing upward, into a groove formed along the longitudinal direction of the guide at approximately the center of the lower surface of the belt guide 30. In the fixing nip portion N that comes into contact with the fixing belt 11, the surface of the sliding member 31d of the ceramic heater 31 and the inner surface of the fixing belt 11 come into sliding contact with each other. As described above, the elastic layer containing silicone rubber has high thermal conductivity in the thickness direction and low hardness in the fixing belt 11. With this configuration, the fixing belt 11 can efficiently heat an unfixed toner image and has low hardness, so that a high-quality image can be fixed onto the recording medium S at the fixing nip.

[0079] As described above, according to one aspect of the present disclosure, a thermal fixing device including a fixing member is provided, and therefore, it is possible to provide a thermal fixing device including a fixing member having excellent fixing performance and image quality. EXAMPLES

[0080] The present invention will be described in more detail below using examples. However, the present invention is not limited to these. In the following, "parts" means "parts by mass." (1) Preparation of liquid addition-curable silicone rubber composition First, 100 parts by mass of a silicone polymer having vinyl groups, which are unsaturated aliphatic groups, only at both ends of the molecular chain and having methyl groups as unsubstituted hydrocarbon groups containing no other unsaturated aliphatic groups, was prepared as component (a). This silicone polymer (trade name: DMS-V35, manufactured by Gelest, viscosity 5000 mm 2 / s) will be referred to as "Vi" from here on. Next, 124 parts by mass of large-diameter metal silicon (product name: #350, manufactured by Kinsei Matec Co., Ltd.) and 41 parts by mass of small-diameter metal silicon (product name: FINE, manufactured by Kinsei Matec Co., Ltd.) were added to this Vi as component (d), and the mixture was placed in a planetary mixer (manufactured by Thinky Corporation, ARV-310) and stirred and mixed at 2000 rpm for 4 minutes to obtain mixture 1. Next, 0.2 parts by mass of 1-ethynyl-1-cyclohexanol (manufactured by Tokyo Chemical Industry Co., Ltd.), which is a cure retarder, was dissolved in the same weight of toluene and added to the mixture 1 to obtain a mixture 2. Next, 0.1 parts by mass of a hydrosilylation catalyst (platinum catalyst: a mixture of 1,3-divinyltetramethyldisiloxane platinum complex, 1,3-divinyltetramethyldisiloxane, and 2-propanol) as component (c) was added to mixture 2 to obtain mixture 3. Furthermore, as component (b), a silicone polymer having a linear siloxane skeleton and having active hydrogen groups bonded to silicon only on the side chain (product name: HMS-301, manufactured by Gelest, viscosity 30 mm 2 1.1 parts by mass of 1.2 parts by mass of 1.25% by mass of 1.25% by mass of 1.25% by mass of 1.25% by mass of 1.1 ...

[0081] (2) Preparation of the fixing belt A stainless steel endless belt with an inner diameter of 24 mm, a width of 400 mm, and a thickness of 30 μm was prepared as a substrate. During the series of manufacturing processes, the endless belt was handled with a core inserted inside. A primer (product name: DY39-051A / B; manufactured by Dow Corning Toray Co., Ltd.) was applied approximately uniformly to the outer peripheral surface of the substrate so that the dry weight was 20 mg. After the solvent was dried, the substrate was baked for 30 minutes in an electric furnace set to 160°C. The silicone rubber composition was applied to the primer-treated substrate by ring coating to a thickness of 250 μm, which is referred to as an uncured endless belt. Next, a corona charger with a charging area width of 295 mm was placed facing the generator of the uncured endless belt, and an AC electric field was applied to the surface of the elastic layer before curing while rotating the uncured endless belt at 100 rpm. The conditions were: current supplied to the discharge wire of the corona charger was ±150 μA, grid electrode potential was ±300 V (Vp-p: 600 V), frequency was 0.025 Hz, charging time was 160 seconds, and the distance between the grid electrode and the belt was 3 mm. This charged uncured endless belt was heated in an electric furnace at 160°C for 1 minute (primary curing), and then heated in an electric furnace at 200°C for 30 minutes (secondary curing) to harden the silicone rubber composition, and then heated in a vacuum drying furnace at 330°C for 5 minutes to obtain an endless belt with an elastic layer. Next, an addition-curing silicone rubber adhesive (product name: SE1819CV A / B; manufactured by Toray Dow Corning Co., Ltd.) was applied almost uniformly to a thickness of about 10 μm as an adhesive layer on the surface of the cured elastic layer of the endless belt. A fluororesin tube (product name: NSE; manufactured by Gunze Co., Ltd.) with an inner diameter of 23 mm and a thickness of 20 μm was laminated on top of this as a release layer while expanding its diameter. After that, the belt surface was uniformly rubbed from above the fluororesin tube to rub out excess adhesive from between the elastic layer and the fluororesin tube until it became thin, about 5 μm. The endless belt was heated for 1 hour in an electric furnace set at 200° C. to harden the adhesive and fix the fluororesin tube onto the elastic layer. Both ends of the obtained endless belt were cut to obtain a fixing belt with a width of 336.5 mm.

[0082] (3) Evaluation of characteristics of the elastic layer of the fixing belt (3-1) Thermal conductivity of the elastic layer in the thickness direction The thermal conductivity λ of the elastic layer in the thickness direction was calculated from the following formula. λ=α×C p ×ρ In the formula, λ is the thermal conductivity of the elastic layer in the thickness direction (W / (m K)), α is the thermal diffusivity in the thickness direction (m 2 / s), C p is the specific heat at constant pressure (J / (kg K)), and ρ is the density (kg / m 3 ) where the thermal diffusivity α in the thickness direction and the specific heat at constant pressure C p The values ​​of and density ρ were obtained by the following method.

[0083] ·Thermal diffusivity α The thermal diffusivity α in the thickness direction of the elastic layer was measured at room temperature (25°C) using a periodic heating method thermal property measurement device (product name: FTC-1, manufactured by Advance Riko Co., Ltd.). Sample pieces with an area of ​​8 × 12 mm were cut from the elastic layer with a cutter to prepare a total of five sample pieces, and the thickness of each sample piece was measured using a digital length measuring device (product name: DIGIMICRO (registered trademark) MF-501 flat probe φ4 mm; manufactured by Nikon Corporation). Next, each sample piece was measured five times in total, and the average value (m 2The measurement was performed while applying pressure to the sample using a 1 kg weight. As a result, the thermal diffusivity α of the silicone rubber elastic layer in the thickness direction was 9.96×10 -7 m 2 / s, it was.

[0084] Constant pressure specific heat C P The constant pressure specific heat of the elastic layer was measured using a differential scanning calorimeter (product name: DSC823e, manufactured by Mettler Toledo K.K.). Specifically, aluminum pans were used as the sample pan and the reference pan. First, for the blank measurement, both pans were empty and kept at a constant temperature of 15°C for 10 minutes, then heated to 215°C at a rate of 10°C / min, and kept at the constant temperature of 215°C for another 10 minutes. The measurements were performed using the same program. Next, 10 mg of synthetic sapphire with a known low-pressure specific heat was used as a reference material, and measurements were performed using the same program. Next, a measurement sample of 10 mg, the same amount as the synthetic sapphire reference material, was cut out from the elastic layer, set in a sample pan, and measurements were performed using the same program. These measurement results were analyzed using the specific heat analysis software attached to the differential scanning calorimeter, and the constant pressure specific heat C at 25°C was calculated from the average of the five measurement results. P was calculated. As a result, the specific heat at constant pressure of the silicone rubber elastic layer was found to be 1.05 J / (g·K).

[0085] ·Density ρ The density of the elastic layer was measured using a dry automatic density meter (product name: Accupyc 1330-01, manufactured by Shimadzu Corporation). 3 A sample cell was used, and a sample piece was cut out from the elastic layer so as to fill approximately 80% of the cell volume. The mass of this sample piece was measured and then placed in the sample cell. This sample cell was set in the measurement section of the device, and helium was used as the measurement gas. After gas replacement, the volume measurement was carried out 10 times. The density of the elastic layer was calculated from the mass of the sample piece and the measured volume for each measurement, and the average value was calculated. As a result, the density of the silicone rubber elastic layer was 1.53 g / cm 3 It was. From the above, the unit converted specific heat of the elastic layer at constant pressure C p (J / (kg K)) and density ρ(kg / m 3 ), and the measured thermal diffusivity α(m 2 The thermal conductivity λ of the elastic layer in the thickness direction was calculated from the thermal conductivity (Tc) of the elastic layer, and was found to be 1.60 W / (m K).

[0086] (3-2) Compressive elastic modulus of elastic layer The compressive modulus of the elastic layer in the thickness direction was measured using a dynamic viscoelasticity measuring device (product name: Rheogel-E4000, manufactured by UBM Co., Ltd.). Specifically, a test piece with an area of ​​50 x 50 mm was cut out from the elastic layer with a cutter. A test was performed five times in which this test piece was compressed in the thickness direction of the elastic layer under the conditions of a frequency of 1 Hz, a strain of 0.05 mm, and an initial strain of 0.02 mm, and the arithmetic average value of the measured values ​​obtained in each test was calculated. This average value was taken as the compressive modulus of the elastic layer in the thickness direction.

[0087] (3-3) Tensile modulus of elastic layer In order to confirm that the elastic layer has a low hardness, the tensile modulus of the elastic layer was measured. Specifically, a punch was used to cut out a sample of the elastic layer according to Japanese Industrial Standards (JIS) K6251:200. A dumbbell-shaped No. 8 test piece for measurement defined in JP-A-2003-2006-13611 was prepared. At this time, the longitudinal direction of the test piece was aligned with the direction (arrow 603 in FIG. 6(a)) perpendicular to the thickness direction (arrow 601 in FIG. 6(b)) of the elastic layer 4. Specifically, the longitudinal direction of the test piece (arrow 603 in FIG. 6) was aligned with the direction perpendicular to the circumferential direction of the fixing belt (direction along the rotation axis). Then, the thickness of the measurement point near the center was measured. Next, the test piece for measurement was tested at room temperature at a tensile speed of 200 mm / min in the direction perpendicular to the thickness direction of the elastic layer, that is, the direction of the arrow 601 in FIG. 6(a) using a tensile tester (apparatus name: Strograph EII-L1, manufactured by Toyo Seiki Seisakusho Co., Ltd.). The tensile modulus of elasticity was determined by creating a graph from the measurement results with the strain of the sample piece on the horizontal axis and the tensile stress on the vertical axis, and linearly approximating the measurement data in the strain range of 0 to 10%. As a result, the tensile modulus of the elastic layer was 0.15 MPa.

[0088] (3-4) Change in hardness of elastic layer when left in 240℃ atmosphere A rectangular parallelepiped sample, 50 mm long, 50 mm wide, and 150 μm thick, was sampled from the elastic layer with a cutter and placed in an atmosphere with an oxygen concentration of 1% or less and a temperature of 240° C. for 100 hours. The compressive elastic modulus of the sample in the thickness direction was measured three times every 10 hours, and the average values ​​of the measured values ​​were designated as H10 to H100. The rate of decrease of each of the compressive elastic modulus H10 to H100 was measured based on the compressive elastic modulus H0 at 0 hours. Specifically, the pressure inside a furnace connected to a vacuum pump was reduced to 0.01 atmospheres or less in order to reduce the oxygen concentration to 1% or less, and then an inert gas was injected. In addition, in order to prevent oxidation due to air replacement when the samples were inserted and removed, each sample was wrapped in aluminum foil before being inserted into and removed from the furnace.

[0089] (4) Actual machine evaluation (fixation, durability, image quality) <Adhesion evaluation> The fixing property was evaluated using a fixing device of the fixing belt-pressure roller heating type in which the prepared fixing film was assembled, as shown in Fig. 8. The pressure roller was rotated so that the moving speed (circumferential speed) of the surface of the pressure roller was 320 mm / sec, with the pressure force at one end being about 156.8 N and the total pressure force being about 313.6 N (32 kgf), and the surface temperature of the paper passing part of the fixing film was controlled to 150 to 180°C. A solid cyan image was formed on plain paper with a basis weight of 81 g / m2 (product name: GF-C081, manufactured by Canon Inc.). Specifically, the fixing temperature of the thermal fixing device was adjusted from 150°C, which is the standard fixing temperature in the copier, to 160°C, and five solid cyan images were formed in succession, and the image density of the fifth solid image was measured. Next, the toner surface of the solid image was rubbed three times in the same direction with Silbon paper with a load of 4.9 kPa (50 g / cm2), and the image density after rubbing was measured. Then, when the reduction rate of image density before and after rubbing (= [image density difference before and after rubbing / image density before rubbing] x 100) was less than 5%, it was determined that the toner was fixed to the cardboard. The results were evaluated according to the following criteria. The image density was measured using a reflection densitometer (manufactured by Macbeth). A: The toner was fixed to the paper at a fixing temperature of 150°C or higher and lower than 155°C. B: The toner was fixed to the paper at a fixing temperature of 155°C or higher and lower than 160°C. C: The toner was fixed to the paper at a fixing temperature of 160° C. or higher.

[0090] <Durability evaluation> With the fixing temperature set to the standard fixing temperature (160°C), cyan solid images were continuously formed on A4-sized plain paper, and the number of sheets at which the elastic layer of the fixing belt was broken or plastically deformed was recorded and evaluated according to the following criteria. If the elastic layer of the fixing belt was still not broken or plastically deformed even after the number of images reached 740,000 sheets, image formation was stopped at 740,000 sheets. A: Even after 740,000 images were formed, no damage or plastic deformation was observed in the elastic layer of the fixing belt. B: No destruction or plastic deformation occurred in the elastic layer of the fixing belt even after 600,000 images were formed, but destruction or plastic deformation occurred in the elastic layer of the fixing belt after 740,000 images were formed. C: The elastic layer of the fixing belt was destroyed or plastically deformed after forming images on less than 600,000 sheets.

[0091] <Image quality evaluation (uneven melting evaluation)> By observing the melted state of the toner after the toner image formed on the paper is fixed, it is possible to obtain an index of the ability of the fixing member to follow the unevenness of the paper. Using the same film heating fixing device 40 as in the durability evaluation, 10 sheets of evaluation images for melting unevenness are fixed in succession under an environment of temperature 10° C. and relative humidity 50%. The paper is A4 size recycled paper (product name: Recycled Paper GF-R100; manufactured by Canon Inc., thickness 92 μm) , basis weight 66g / m2, recycled paper content 70%, Beck smoothness 23 seconds (JIS P8119 compliant The uneven melting evaluation image is an image in which a 10 mm x 10 mm patch image formed with cyan toner and magenta toner at 100% concentration is placed near the center of the paper. As a guide for uneven melting, sufficient heat and pressure must be applied to the image area where two colors are formed, causing the toner to melt and mix. In particular, in the concave areas of the paper unevenness, if heat is applied but no pressure is applied, the grain boundaries of the toner remain after fixing, causing uneven melting without sufficient color mixing. If the fixing member cannot conform to the unevenness sufficiently, pressure is applied to the convex areas, causing color mixing, but in the concave areas, color mixing is insufficient. Therefore, the ability to conform to unevenness is judged based on the image formation. This was confirmed by observing the molten state of the area. After printing 10 sheets of images in succession to evaluate uneven melting, the 10th sheet was taken as a sample and the image-formed area was observed under an optical microscope to evaluate uneven melting. The evaluation criteria were as follows: (Evaluation Criteria) A: The toner grain boundaries are not visible even in the recesses of the paper fibers, and the colors are mixed in both the recesses and protrusions. B: Although some toner grain boundaries are observed in the recesses of the paper fibers, the color is mostly mixed in both the recesses and protrusions. C: Only the convex parts of the paper fibers are mixed, and many toner grain boundaries are observed in the concave parts.

[0092] [Example 2] A fixing belt was produced and evaluated in the same manner as in Example 1, except that the time for electric field orientation was set to 10 s.

[0093] [Example 3] A fixing belt was produced and evaluated in the same manner as in Example 1, except that after the elastic layer was formed and heated in an electric furnace at 200°C for 30 minutes (secondary curing) to cure the silicone rubber composition, the temperature for the further high-temperature heat treatment was set to 280°C.

[0094] [Example 4] A fixing belt was prepared and evaluated in the same manner as in Example 1, except that 103 parts by weight of large-diameter metal silicon (product name: #350, manufactured by Kinsei Matec Co., Ltd.) and 62 parts by weight of small-diameter metal silicon (product name: FINE, manufactured by Kinsei Matec Co., Ltd.) were added.

[0095] [Example 5] A fixing belt was prepared and evaluated in the same manner as in Example 1, except that 177 parts by weight of large-diameter metal silicon (product name: #350, manufactured by Kinsei Matec Co., Ltd.) and 12 parts by weight of small-diameter metal silicon (product name: FINE, manufactured by Kinsei Matec Co., Ltd.) were added.

[0096] [Comparative Example 1] A fixing belt was produced and evaluated in the same manner as in Example 1, except that the amount of the crosslinking agent (SiH) was 1.4 parts.

[0097] [Comparative Example 2] A fixing belt was produced and evaluated in the same manner as in Example 1, except that the electric field alignment treatment was not performed.

[0098] [Comparative Example 3] A fixing belt was produced and evaluated in the same manner as in Example 1, except that after the elastic layer was formed and heated in an electric furnace at 200°C for 30 minutes (secondary curing) to harden the silicone rubber composition, no further heat treatment at a high temperature was performed.

[0099] The above results are shown in Tables 1 and 2. [Table 1] [Table 2] In Tables 1 and 2, the "hardness change" values ​​indicate the results of the hardness change when the elastic layer is left in an atmosphere at 240°C, and indicate the rate of decrease of the compressive elastic modulus values ​​H10 to H100 every 10 hours relative to the compressive elastic modulus value H0 at 0 hours. A negative rate of decrease indicates that the compressive elastic modulus is increasing relative to H0.

[0100] In all of the examples, good results were obtained in terms of fixation, durability, and image quality, with ratings of A or B. The lower the tensile modulus of elasticity, the better the image quality, and the smaller the ratio of tensile modulus of elasticity / compressive modulus of elasticity, the higher the thermal conductivity and the better the fixation. On the other hand, the comparative example received a C rank in any of the following categories: fixation, durability, or image quality.

[0101] The present disclosure relates to the following configurations. (Configuration 1) An electrophotographic member having a substrate and an elastic layer on an outer peripheral surface of the substrate, The elastic layer contains silicone rubber, The elastic layer has a tensile modulus of 0.20 MPa or less in a direction perpendicular to the thickness direction, The compressive elastic modulus of the elastic layer in the thickness direction is 0.19 to 0.57 MPa; the ratio of the tensile elastic modulus in a direction perpendicular to the thickness direction to the compressive elastic modulus in the thickness direction of the elastic layer (tensile elastic modulus / compressive elastic modulus) is 0.80 or less; A rectangular parallelepiped specimen having a length of 50 mm, a width of 50 mm, and a thickness of 150 μm is sampled from the elastic layer, and compressed in an atmosphere having an oxygen concentration of 1% by volume or less and a temperature of 240° C. for 10 hours at intervals of 10 hours up to 100 hours. The compressive moduli of the specimen in the direction corresponding to the thickness direction of the elastic layer are defined as H0 to H100, respectively, with the compressive moduli H0 being the standard. An electrophotographic member, characterized in that the rate of decrease in each of H10 to H100 is 5% or less. (Configuration 2) 2. The electrophotographic member according to claim 1, wherein the silicone rubber comprises a cured product of an addition-curing type silicone rubber composition. (Configuration 3) The elastic layer was used as a sample. 29 3. The electrophotographic member according to claim 1, wherein in a chart obtained by Si-NMR measurement, the ratio of the integral value of the peak corresponding to the T unit to the integral value of the peak corresponding to the D unit (T unit / D unit) is 0.030 or more. (Configuration 4) 4. The electrophotographic member according to any one of configurations 1 to 3, wherein when the silicone rubber is heated at 150° C. for 1 hour, the total amount of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, and decamethylcyclopentasiloxane generated is 1.5 ppm or more. (Configuration 5) 5. The electrophotographic member according to any one of configurations 1 to 4, wherein the elastic layer contains a filler, and the filler content in the elastic layer is 30 vol % or more and less than 50 vol % based on the silicone rubber. (Configuration 6) when binary images of 150 μm×100 μm in any five locations on a first cross section in the thickness-circumferential direction of the elastic layer and binary images of 150 μm×100 μm in any five locations on a second cross section in the thickness-axial direction of the elastic layer are obtained, the average value of the area ratio of large particle size filler having a circle equivalent diameter of 5 μm or more in each of a total of 10 binary images is 20% or more and 40% or less, The average degree of orientation fL of the large particle size filler is 0.00 or more and 0.15 or less, the average area ratio of small particle size filler particles having an equivalent circle diameter of less than 5 μm in each of the binarized images is 10% or more and 20% or less; The average degree of orientation fS of the small particle size filler is 0.20 or more and 0.50 or less, 6. The electrophotographic member according to embodiment 5, wherein the small particle size filler has an average arrangement angle ΦS of 60° or more and 120° or less. (Configuration 7) 7. The electrophotographic member according to any one of Configurations 1 to 6, wherein the electrophotographic member is a fixing member having an endless shape. (Configuration 8) 8. The electrophotographic member according to any one of configurations 1 to 7, wherein the electrophotographic member is a pressure member having an endless shape. (Configuration 9) A heat fixing device in an electrophotographic image forming apparatus, The heat fixing device includes a fixing member and a pressure member disposed opposite the fixing member, 9. A heat fixing device, wherein at least one of the fixing member and the pressure member is the electrophotographic member according to any one of Configurations 1 to 8. (Configuration 10) An electrophotographic image forming apparatus including a heat fixing device, The heat fixing device includes a fixing member and a pressure member disposed opposite the fixing member, 9. An electrophotographic image forming apparatus, wherein at least one of the fixing member and the pressure member is the electrophotographic member according to any one of Configurations 1 to 8. [Industrial Applicability]

[0102] As described above, the present disclosure can be used as an electrophotographic member that achieves a low hardness state while ensuring thermal conductivity and durability in the thickness direction of the elastic layer of a fixing member. [Explanation of symbols]

[0103] 1 core, 2 corona charger, 3 base body, 4 elastic layer, 5 adhesive layer, 6 surface layer, 7 large particle size filler, 8 small particle size filler 100 fixing member, 201 front block, 202 rear block, 203, 204 shield, 205 discharge wire, 206 grid, 401 sample, 401-1 first cross section, 401-2 second cross section 11 fixing belt, 12 pressure belt, 13 induction heating member 13a induction coil, 13b excitation core, 13c coil holder 14 Excitation circuit, 15 Temperature detection element, 16 Control circuit section, 17 Roller 18 heating side roller, 19 tension roller, 20 pressure side roller 21 fixing pad, 22 pressure pad, 23, 24 sliding sheet 25 Separation member, 30 Belt guide, 31 Ceramic heater 31a heater substrate, 31b heat generating layer, 31c protective layer, 31d sliding member 32 stay, 33 pressure roller, 33a core metal, 33b elastic layer 34 Temperature detection element N fixing nip, t unfixed toner, S recording medium, M motor

Claims

1. An electrophotographic member having a substrate and an elastic layer on an outer peripheral surface of the substrate, The elastic layer contains silicone rubber, The elastic layer has a tensile modulus of 0.20 MPa or less in a direction perpendicular to the thickness direction, The compressive elastic modulus of the elastic layer in the thickness direction is 0.19 to 0.57 MPa; the ratio of the tensile elastic modulus in a direction perpendicular to the thickness direction to the compressive elastic modulus in the thickness direction of the elastic layer (tensile elastic modulus / compressive elastic modulus) is 0.80 or less; A rectangular parallelepiped sample having a length of 50 mm, a width of 50 mm and a thickness of 150 μm is sampled from the elastic layer, and is subjected to an oxygen concentration of 1% by volume or less and an atmosphere at a temperature of 240° C. for 10 hours at intervals of 10 hours up to 100 hours. When the compressive moduli of the sample in a direction corresponding to the thickness direction of the elastic layer are each defined as compressive moduli H0 to H100, the reduction rate of each of the compressive moduli H10 to H100 is 5% or less based on the compressive moduli H0.

2. 2. The electrophotographic member of claim 1, wherein said silicone rubber comprises a cured product of an addition-curing type silicone rubber composition.

3. The elastic layer was used as a sample. 29 2. The electrophotographic member according to claim 1, wherein in a chart obtained by Si-NMR measurement, a ratio of an integral value of a peak corresponding to T units to an integral value of a peak corresponding to D units (T units / D units) is 0.030 or more.

4. 2. The electrophotographic member of claim 1, wherein the total amount of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane and decamethylcyclopentasiloxane generated from said silicone rubber when heated at 150[deg.] C. for 1 hour is 1.5 ppm or more.

5. 2. The electrophotographic member of claim 1, wherein said elastic layer contains a filler, and the filler content in said elastic layer is 30 vol % or more and less than 50 vol % based on said silicone rubber.

6. when binary images of 150 μm×100 μm in any five positions on a first cross section in the thickness-circumferential direction of the elastic layer and binary images of 150 μm×100 μm in any five positions on a second cross section in the thickness-axial direction of the elastic layer are obtained, the average value of the area ratio of large particle size filler having a circle equivalent diameter of 5 μm or more in each of a total of 10 binary images is 20% or more and 40% or less, The average degree of orientation fL of the large particle size filler is 0.00 or more and 0.15 or less, the average area ratio of small particle size filler particles having an equivalent circle diameter of less than 5 μm in each of the binarized images is 10% or more and 20% or less; The average degree of orientation fS of the small particle size filler is 0.20 or more and 0.50 or less, 6. The electrophotographic member according to claim 5, wherein the small particle size filler has an average arrangement angle .PHI.S of 60.degree. or more and 120.degree. or less.

7. 2. The electrophotographic member of claim 1, wherein said electrophotographic member is a fuser member having an endless shape.

8. 2. The electrophotographic member of claim 1, wherein said electrophotographic member is a pressure member having an endless shape.

9. A heat fixing device in an electrophotographic image forming apparatus, The heat fixing device includes a fixing member and a pressure member disposed opposite the fixing member, At least one of the fixing member and the pressure member is A heat fixing device which is an electrophotographic member.

10. An electrophotographic image forming apparatus including a heat fixing device, The heat fixing device includes a fixing member and a pressure member disposed opposite the fixing member, 9. An electrophotographic image forming apparatus, wherein at least one of said fixing member and said pressure member is the electrophotographic member according to claim 1.

Citation Information

Patent Citations

  • Fixing member and fixing device

    JP2005300591A

  • Fixing member and thermal fixing device

    JP2019215531A